Frontend Design and Development of Thesis Management Application Using NextJS in Physics Study Program UPN “Veteran” Jatim - Nur Cahyo Wibowo; Adimas Syiraa Setiabudhi; Eka Dyar Wahyuni (Universitas Islam Kuantan Singingi, 2025)
In higher education institutions, managing undergraduate thesis administration remains a challenge, particularly in the Physics Study Program, which currently lacks an system that can manage the process of students thesis. To address this issue, the Thesis Management Application was developed as a solution to manage thesis administration through a web-based system accessible to Students, Lecturers, Thesis Coordinators, and Study Program Coordinator. This study focuses on frontend web development using the Next.js framework and APIs. The application offers key features including authentication, pre-proposal submission, thesis advisor assignment, seminar and examination management, and submission of graduation documents. The development process followed the Scrum methodology over six sprint iterations. The application was tested using both black-box testing and user acceptance testing. A total of 177 were tested using black-box testing, all of which received a passed status. User Acceptance Testing was conducted across the four user roles mentioned earlier, with all features receiving accepted status Finally, the system was deployed on the Vercel cloud hosting server, allowing public access for users.